ANALISIS KINERJA KEUANGAN DAN HARGA SAHAM PERBANKAN DI INDONESIA - Januar Eko Prasetio; Ario Dananjaya (Jurnal Keuangan dan Perbankan, 2008)
This research aimed at finding out the differences on Loan to Deposit Ratio (LDR),Return on Asset (ROA), Return on Equity (ROE), Operation Expenses to Revenues OperationRatio Capital Adequacy Ratio (CAR), and stock price between Government Banking, NationalBanking, and Foreign Banking at the Jakarta Stock Exchange (JSX). The hypothesis was analyzedby using ANOVA test. The result showed that there was not difference on Loan to DepositRatio (LDR), Return on Asset (ROA), Return on Equity (ROE), Operation Expenses to RevenuesOperation Ratio Capital Adequacy Ratio (CAR), and stock price between Government Banking,National Banking, and Foreign Banking